Quercus ilex L. as bioaccumulator for heavy metals in urban areas: Effectiveness of leaf washing with distilled water and considerations on the trees distance from traffic - Ugolini, Francesca; Tognetti, Roberto; Raschi, Antonio; Bacci, Laura (Urban Forestry & Urban Greening, 2013)
In recent years the use of plants as bioaccumulators or bioindicators has increased because enable the prediction of pollution for monitoring purposes, even in urban environments where traffic is a major source of heavy metals pollution. In this study we hypothesized holm oak (Quercus ilex L.) a valid trapping species for heavy metals. We also hypothesized that metals capture capacity by deposition on the crown is connected to the surrounding environmental characteristics and the distance of trees from the source of pollution. The study was conducted in the city of Florence. Holm oaks were selected in different sites near to heavy traffic roads. Concentrations of Zn, Pb, Cd, Cu, Fe, Mn, Cr, and Ba were analyzed through two methods: leaf washing with distilled water and leaf unwashing. One-year-old leaves (new leaves) were also compared with previous-year leaves (old leaves). Our results demonstrated the good capacity of this species to capture heavy metals (Pb, Fe, Mn, Cr, and Ba), particularly due to the presence of old leaves, which enhance the crown deposition surface. Washing was effective and it allowed testing the behaviour with regard to microelements: new leaves showed high Cu concentration, while old leaves had high Pb concentration. The dispersion of metals through the atmosphere was assessed through regression analysis, in two comparable gardens: leaves at farther distance from the traffic were richer in Zn, Pb, Mn, and Ba. The physical context of the surrounding environment was probably altering the distribution of heavy metals as barriers to dispersion, which can reach tens of metres from the source of pollution. Therefore, this work suggests that wind modelling and trees distribution and characteristics should be taken into consideration to evaluate the pollutants dispersion, especially for planning of recreational urban green areas.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: Deposition; Heavy metals; Holm oak; Internal concentration; Traffic pollution; Urban environment

Quercus ilex L. as bioaccumulator for heavy metals in urban areas: Effectiveness of leaf washing with distilled water and considerations on the trees distance from traffic - Ugolini, Francesca; Tognetti, Roberto; Raschi, Antonio; Bacci, Laura (Urban Forestry & Urban Greening, 2013)
In recent years the use of plants as bioaccumulators or bioindicators has increased because enable the prediction of pollution for monitoring purposes, even in urban environments where traffic is a major source of heavy metals pollution. In this study we hypothesized holm oak (Quercus ilex L.) a valid trapping species for heavy metals. We also hypothesized that metals capture capacity by deposition on the crown is connected to the surrounding environmental characteristics and the distance of trees from the source of pollution. The study was conducted in the city of Florence. Holm oaks were selected in different sites near to heavy traffic roads. Concentrations of Zn, Pb, Cd, Cu, Fe, Mn, Cr, and Ba were analyzed through two methods: leaf washing with distilled water and leaf unwashing. One-year-old leaves (new leaves) were also compared with previous-year leaves (old leaves). Our results demonstrated the good capacity of this species to capture heavy metals (Pb, Fe, Mn, Cr, and Ba), particularly due to the presence of old leaves, which enhance the crown deposition surface. Washing was effective and it allowed testing the behaviour with regard to microelements: new leaves showed high Cu concentration, while old leaves had high Pb concentration. The dispersion of metals through the atmosphere was assessed through regression analysis, in two comparable gardens: leaves at farther distance from the traffic were richer in Zn, Pb, Mn, and Ba. The physical context of the surrounding environment was probably altering the distribution of heavy metals as barriers to dispersion, which can reach tens of metres from the source of pollution. Therefore, this work suggests that wind modelling and trees distribution and characteristics should be taken into consideration to evaluate the pollutants dispersion, especially for planning of recreational urban green areas.
Keywords: Deposition; Heavy metals; Holm oak; Internal concentration; Traffic pollution; Urban environment

Nitrogen dioxide (NO2) uptake by vegetation controlled by atmospheric concentrations and plant stomatal aperture - Chaparro-Suarez, I. G.; Meixner, F. X.; Kesselmeier, J. (Atmospheric Environment, 2011)
Nitrogen dioxide (NO2) exchange between the atmosphere and ﬁve European tree species was investigated in the laboratory using a dynamic branch enclosure system (consisting of two cuvettes) and a highly speciﬁc NO2 analyzer. NO2 measurements were performed with a sensitive gas phase chemiluminescence NO detector combined with a NO2 speciﬁc (photolytic) converter, both from Eco-Physics (Switzerland). This highly speciﬁc detection system excluded bias from other nitrogen compounds. Investigations were performed at two light intensities (Photosynthetic Active Radiation, PAR, 450 and 900 mmol m2 s 1 ) and NO2 concentrations between 0 and 5 ppb. Ambient parameters (air temperature and relative humidity) were held constant. The data showed dominant NO2 uptake by the respective tree species under all conditions. The results did not conﬁrm the existence of a compensation point within a 95% conﬁdence level, though we cannot completely exclude emission of NO2 under very low atmospheric concentrations. Induced stomatal stricture, or total closure, by changing light conditions, as well as by application of the plant hormone ABA (Abscisic Acid) caused a corresponding decrease of NO2 uptake. No loss of NO2 to plant surfaces was observed under stomatal closure and species dependent differences in uptake rates could be clearly related to stomatal behavior
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Deposition; Gas exchange; Nitrogen dioxide; Stomatal uptake; Vegetation

Assessing the risk caused by ground level ozone to European forest trees: a case study in pine, beech and oak across different climate regions. - Emberson, Lisa D; Büker, Patrick; Ashmore, Mike R (Environmental pollution (Barking, Essex : 1987), 2007)
Two different indices have been proposed for estimation of the risk caused to forest trees across Europe by ground-level ozone, (i) the concentration based AOT40 index (Accumulated Over a Threshold of 40 ppb) and (ii) the recently developed flux based AFstY index (Accumulated stomatal Flux above a flux threshold Y). This paper compares the AOT40 and AFstY indices for three forest trees species at different locations in Europe. The AFstY index is estimated using the DO(3)SE (Deposition of Ozone and Stomatal Exchange) model parameterized for Scots pine (Pinus sylvestris), beech (Fagus sylvatica) and holm oak (Quercus ilex). The results show a large difference in the perceived O(3) risk when using AOT40 and AFstY indices both between species and regions. The AOT40 index shows a strong north-south gradient across Europe, whereas there is little difference between regions in the modelled values of AFstY. There are significant differences in modelled AFstY between species, which are predominantly determined by differences in the timing and length of the growing season, the periods during which soil moisture deficit limits stomatal conductance, and adaptation to soil moisture stress. This emphasizes the importance of defining species-specific flux response variables to obtain a more accurate quantification of O(3) risk.
Keywords: Beech (Fagus sylvatica); Critical levels; Deposition; Flux; Forests; Holm oak (Quercus ilex); Ozone; Scots pine (Pinus sylvestris); stomata

Assessing the risk caused by ground level ozone to European forest trees: a case study in pine, beech and oak across different climate regions. - Emberson, Lisa D.; Büker, Patrick; Ashmore, Mike R. (Environmental pollution (Barking, Essex : 1987), 2007)
Two different indices have been proposed for estimation of the risk caused to forest trees across Europe by ground-level ozone, (i) the concentration based AOT40 index (Accumulated Over a Threshold of 40 ppb) and (ii) the recently developed flux based AFstY index (Accumulated stomatal Flux above a flux threshold Y). This paper compares the AOT40 and AFstY indices for three forest trees species at different locations in Europe. The AFstY index is estimated using the DO(3)SE (Deposition of Ozone and Stomatal Exchange) model parameterized for Scots pine (Pinus sylvestris), beech (Fagus sylvatica) and holm oak (Quercus ilex). The results show a large difference in the perceived O(3) risk when using AOT40 and AFstY indices both between species and regions. The AOT40 index shows a strong north-south gradient across Europe, whereas there is little difference between regions in the modelled values of AFstY. There are significant differences in modelled AFstY between species, which are predominantly determined by differences in the timing and length of the growing season, the periods during which soil moisture deficit limits stomatal conductance, and adaptation to soil moisture stress. This emphasizes the importance of defining species-specific flux response variables to obtain a more accurate quantification of O(3) risk.
The following values have no corresponding Zotero field: accession-num: 17412465
Keywords: Beech (Fagus sylvatica); Critical levels; Deposition; Flux; Forests; Holm oak (Quercus ilex); Ozone; Scots pine (Pinus sylvestris); stomata